KERJASAMA INDONESIA - UNITED NATIONS CHILDREN’S FUND (UNICEF) DALAM MENANGANI STUNTING DI NUSA TENGGARA TIMUR TAHUN 2015-2018 - Aprilia Atika Putri; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The United Nations Children's Fund (UNICEF) is one of several international NGOs committed to safeguarding children across the world. One of the United Nations' many bodies, UNICEF works to ensure that children everywhere have the protection and opportunities they deserve. Because of its high prevalence, stunting is a top priority for the Indonesian government in the province of NTT. UNICEF, a global organization focused on child issues, works with the province of NTT to combat stunting via initiatives like the Integrated Malnutrition Management program, which runs from 2015 to 2018. This presentation will discuss UNICEF's Integrated Malnutrition Management program for 2015-2018 and how it has helped reduce the prevalence of stunting in children in NTT. This study adopts the Pluralist stance, which holds that states are not the only actors in international relations, and is driven by the International Organizations theory, which elucidates the significant role that international organizations play. The approach is qualitative, and information is gathered through the official website www.unicef.org as well as research in many books, magazines, and dissertations from the library's collection. The data presented here demonstrates UNICEF's involvement and contributions to the fight against stunting in Indonesia from 2015 to 2018. UNICEF's collaboration and involvement is shown by the provision of aid to malnourished and stunted children in Indonesia, particularly in East Nusa Tenggara Province, which has the highest prevalence of stunting in the country. Keywords: UNICEF, Failing to Thrive, Malnutrition, Cooperation, East Nusa Tenggara, Prevalence, Stunting (UNICEF)